2014
DOI: 10.1039/c4ra10377g
|View full text |Cite
|
Sign up to set email alerts
|

Protein binding and biological evaluation of a polymer-anchored cobalt(iii) complex containing a 2,2′-bipyridine ligand

Abstract: The molecular interaction of polymer-anchored cobalt(III) complex, cis-[Co(bpy) 2 (BPEI)Cl]Cl 2 $4H 2 O (bpy ¼ 2,2 0 -bipyridine, BPEI ¼ branched polyethyleneimine) with two plasma proteins, human serum albumin (HSA) and bovine serum albumin (BSA) using various spectrophotomeric techniques has been investigated. The steady-state and time-resolved fluorescence spectra clearly demonstrated the static quenching mechanism. The calculated thermodynamic parameters revealed that the interaction between the polymer-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…Hoechst staining has uncovered the deviations in cell cytology, with the unique reference to cytoplasm and core center at significant level recognizing the apoptosis. The CP‐SD‐SLN observation showed early apoptotic highlights, such as cell shrinkage, chromatin buildup, and discontinuity as seen in treated cells, and small quantities of necrotic cells (Vignesh et al, ) were observed (Figure b). After treatment with the IC 50 concentration of the SD for 24 h, the cells were viewed for cytological changes.…”
Section: Resultsmentioning
confidence: 90%
“…Hoechst staining has uncovered the deviations in cell cytology, with the unique reference to cytoplasm and core center at significant level recognizing the apoptosis. The CP‐SD‐SLN observation showed early apoptotic highlights, such as cell shrinkage, chromatin buildup, and discontinuity as seen in treated cells, and small quantities of necrotic cells (Vignesh et al, ) were observed (Figure b). After treatment with the IC 50 concentration of the SD for 24 h, the cells were viewed for cytological changes.…”
Section: Resultsmentioning
confidence: 90%
“…Recently, they found that the side-chain polymer formed by the simple bipyridine ligand showed better antibacterial and antifungal activities against some human pathogenic microorganisms, such as S. aureus , Bacillus subtillis , E. coli , Pseudomonas auregenosa and Candida albicans . 160 …”
Section: Metal-containing Polymeric Drugs and Biocidesmentioning
confidence: 99%
“…[3][4][5][6] The affinity to serum albumins has a decisive significance in the development of new medicines. [7,8] Bovine serum albumin (BSA) and human serum albumin (HSA) are the most studied proteins among other blood plasma proteins. [8] Studies of the supramolecular binding of drugs with the proteins of the albumin class are extremely important for obtaining the information on structural features of these complexes determining the therapeutic effect of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Bovine serum albumin (BSA) and human serum albumin (HSA) are the most studied proteins among other blood plasma proteins. [8] Studies of the supramolecular binding of drugs with the proteins of the albumin class are extremely important for obtaining the information on structural features of these complexes determining the therapeutic effect of drugs. [5,6] Moreover, a great attention has lately been paid to elaboration of the methods of targeted delivery (transfer) of drugs in the human body by means of interaction of the target compound with proteins and DNA, [9,10] in particular, to tumors or inflammation nidi.…”
Section: Introductionmentioning
confidence: 99%